RINTISAN PERADABAN PROFETIK UMAT MANUSIA MELALUI PERISTIWA TURUNNYA ADAM AS KE-DUNIA - Saihu Saihu (Institut PTIQ Jakarta, 2019)
This paper discusses the history of the fall of the Prophet Adam AS to the world which was allegedly a prophetic pioneering of human civilization. The writing focuses on tracing the causes of the decline of the Prophet Adam, whether the decline of the Prophet Adam was caused by a mistake he made, namely eating khuldi fruit, or indeed God's will he was sent down to earth even without making mistakes. Sources of data obtained through observation in several books and verses as well as the interpretation of the Qur'an related to the themes discussed. In analyzing the themes discussed, this paper uses several commentators' thoughts, including al-Tabari (838-923 M), al-Qurtubi (1214-1273 M), and M. Quraish Shihab. The writings show that the story of the Prophet Adam AS is a cycle of life in the history of human civilization until the end of time. Humans must reflect on the life story of Adam, that human glory lies in knowledge and obedience to God's commands. While the fall of man is when he forgets the teachings of God and low morality. As mentioned by Ibn Khaldun, every civilization has the same pattern and cycle, namely; pioneering, building, setbacks, destruction.